All-Inorganic CsPbBr3 nanocrystals: gram-scale mechanochemical synthesis and selective photocatalytic CO2 reduction to methane - Kumar,S; Regue,M; Isaacs,M; Freeman,E; Eslava,S (ACS Applied Energy Materials, 2020)
Halide perovskite CsPbBr3 has recently gained wide interest for its application in solar cells, optoelectronics and artificial photosynthesis, but further progress is needed to develop greener and more scalable synthesis procedures and for their application in humid environments. Herein, we report a fast and convenient mechanochemical synthesis of CsPbBr3 perovskite nanocrystals with scale-up capability and control over crystal size and morphology. These perovskite nanocrystals show excellent crystallinity and tunable morphologies, from nanorods to nanospheres and nanosheets, simply changing the mechanochemical reaction conditions such as ball milling time, ball size and Cs precursor. Furthermore, we explore their use for gas-phase photocatalytic CO2 reduction using water vapor as proton source. A photocatalytic conversion of CO2 and H2O(g) to 0.43 (0.03) μmol CH4 g-1 h-1, 2.25 (0.09) μmol CO g-1 h-1 and 0.08 (0.02) μmol H2 g-1 h-1 was for example achieved with CsPbBr3 nanosheets and simulated sunlight, keeping 30% of this activity over three consecutive cycles. When these CsPbBr3 nanosheets were mechanochemically prepared together with Cu-loaded reduced graphene oxide (Cu-RGO), the photocatalytic activity significantly improved to 12.7 (0.95) μmol CH4 g-1 h-1, 0.46 (0.11) μmol CO g-1 h-1 and 0.27 (0.02) μmol H2 g-1 h-1, and a 90% of this activity was retained over three consecutive cycles. The selectivity for CH4 increased to 98.5(0.93)% on an electron basis and a remarkable apparent quantum efficiency of 1.10(0.15)% at 523 nm was achieved. This enhanced activity, selectivity and stability were assigned to the better charge separation, visible light absorption, CO2 adsorption & activation, and hydrophobic character of the obtained composites. These results will contribute to the rational design and application of halide perovskites for CO2 photocatalytic reduction.